Arranjos domiciliares e arranjos nucleares no Brasil: Classificaç\~ao e evoluç\~ao de 1977 a 1998 - Marcelo Medeiros Coelho de Souza; Rafael Guerreiro Osorio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– The article examines the evolution of the Brazilian household arrangements between 1977 and 1988 using PNAD (Brazilian National Household Surveys). It discusses the concepts used in the PNAD and classifies the household arrangements according to kinship relationships of its members. There is in Brazil a tendency of the households to be the residence of members of a single family. Such tendency, however, must not be taken as a sign of convergence of characteristics of the household arrangements or its nuclearization, as the composition of the household arrangements is slowly changing from the "nuclear family" pattern towards the so called "extended family arrangements".
Keywords: 330